1987
DOI: 10.1104/pp.84.4.979
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization and the Sensitivity of Phosphoenolpyruvate Carboxylase to Inactivation by Proteinases

Abstract: Phosphenolpyruvate (PEP) carboxylase from leaves of Crassula argentea displays varying levels of sensitivity to inactivation by various proteolytic enzymes. In general, the native enzyme is sensitive to proteinases known to attack at the carbonyl end of lysine or arginine (trypsin, papain, or bromelain). The ineffective proteolytic enzymes are those which have low specificity or which attack at the N-terminal end of hydrophobic amino acids, or which cannot attack lysine. The lack of an effect of endoproteinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…The CAM enzyme, which here reaches (18)(19)(20). However, is it possible to obtain data from experiments carried out as in Figure 1 which will support the hypothesis that the differential responses seen in Figure 1 and in Table I Figure 1 using enzyme which had been preincubated for 30 min in the standard suspending medium with 20% (w/v) glycerol.…”
Section: Ph Profile Of Maximal Inhibition By Malatementioning
confidence: 62%
See 1 more Smart Citation
“…The CAM enzyme, which here reaches (18)(19)(20). However, is it possible to obtain data from experiments carried out as in Figure 1 which will support the hypothesis that the differential responses seen in Figure 1 and in Table I Figure 1 using enzyme which had been preincubated for 30 min in the standard suspending medium with 20% (w/v) glycerol.…”
Section: Ph Profile Of Maximal Inhibition By Malatementioning
confidence: 62%
“…This difference was found between enzyme prepared from CAM leaves gathered just before daylight or late in the afternoon (26), and the convertibility of the dimer to the tetramer and the resistance of the tetramer to malate inhibition and the susceptibility of the dimer to malate has been demonstrated (19,20,27,29).…”
Section: Discussionmentioning
confidence: 97%
“…Some workers do not find changes in the size of the molecule under conditions that are thought to result in different activities. We and others using HPLC and light scattering have found that PEPC has a diurnal change in size (1,17,18) and aggregates or disaggregates under the influence of ligands and other treatments that result in differing activities (10,(12)(13)(14).…”
mentioning
confidence: 95%
“…It has been suggested that producing a highly purified PEPC requires such a long preparation time that it may result in the loss by action of proteinases of the N-terminal segment that contains the seryl group that is phosphorylated (3), thus eliminating the possibility of control by phosphorylation. An opposing sug-gestion is that incubation of the CAM PEPC with trypsin causes a decrease in activity (13), but the residual activity is still inhibited by malate and activated by Glc-6-P, making it unlikely that some crucial regulatory site has been removed.…”
mentioning
confidence: 99%
“…The fluorescence of the extrinsic fluorophore ANS was measured with a Perkin Elmer LS-5 spectrofluorimeter in a 3-mL cuvette thermostated at 25°C and magnetically stirred (19). ANS was excited at 350 nm (slit = 5 nm) and emission was measured at 490 nm (slit = 15 nm).…”
Section: Fluorescence Measurementsmentioning
confidence: 99%